2012
DOI: 10.2147/ijn.s28538
|View full text |Cite
|
Sign up to set email alerts
|

Impact of heat treatment on size, structure, and bioactivity of elemental selenium nanoparticles

Abstract: Background: Elemental selenium nanoparticles have emerged as a novel selenium source with the advantage of reduced risk of selenium toxicity. The present work investigated whether heat treatment affects the size, structure, and bioactivity of selenium nanoparticles. Methods and results: After a one-hour incubation of solution containing 80 nm selenium particles in a 90°C water bath, the nanoparticles aggregated into larger 110 nm particles and nanorods (290 nm × 70 nm), leading to significantly reduced bioavai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 49 publications
(64 reference statements)
3
21
0
2
Order By: Relevance
“…The aggregates comprising numerous single SeNPs were actually dark bulks that appeared during the long-term preservation. However, the narrow size distribution, highly faceted morphology and uniform edge-to-edge distances between particles induced by heating 40 nm SeNPs 38 were not found among these enlarged SeNPs shown in Figure 2C and D. Perhaps, sharp reconstruction of original SeNPs could not be triggered under such a mild storage condition (25°C). However, size enlargement and agglomeration of SeNPs seemed to be unavoidable in an aqueous environment.…”
Section: Stability Of Cts-senpsmentioning
confidence: 93%
See 1 more Smart Citation
“…The aggregates comprising numerous single SeNPs were actually dark bulks that appeared during the long-term preservation. However, the narrow size distribution, highly faceted morphology and uniform edge-to-edge distances between particles induced by heating 40 nm SeNPs 38 were not found among these enlarged SeNPs shown in Figure 2C and D. Perhaps, sharp reconstruction of original SeNPs could not be triggered under such a mild storage condition (25°C). However, size enlargement and agglomeration of SeNPs seemed to be unavoidable in an aqueous environment.…”
Section: Stability Of Cts-senpsmentioning
confidence: 93%
“…6,17 Obviously, the morphology of SeNPs could be easily mediated by CTS. A smaller size of CTS-SeNPs, however, might be preferred instead of the bigger ones, since better thermostability, 38 more powerful antioxidant activities, 6 and more potent chemopreventive abilities 17 could be achieved.…”
mentioning
confidence: 99%
“…1A, C). To obtain larger sized SeNPs, the small-sized SeNPs were heated at 70 C for 10 h after Zhang et al (2012), who demonstrated that heat treatment increases SeNP dimensions. The resultant large-sized SeNPs were an average of 91 nm, as indicated by both TEM and DLS (Fig.…”
Section: Preparation Of Selenium Nanoparticlesmentioning
confidence: 99%
“…Otherwise, the thermal stability of Se nanoparticles as a type of nanoscale biomaterial remains unknown. Thus, the thermostability of Se nanoparticles is sizedependent, smaller Se nanoparticles being more resistant than larger Se nanoparticles to transformation into nanorods during heat treatment as reviewed by Zhang et al ( 2012 ).…”
Section: Red Elemental Selenium Nanoparticles In Higher Plantsmentioning
confidence: 99%